A simple, rapid, and reliable protocol to localize hydrogen peroxide in large plant organs by DAB-mediated tissue printing - Liu, Yong-Hua; Offler, Christina E.; Ruan, Yong-Ling (Frontiers in Plant Science, 2014)
Hydrogen peroxide (H2O2) is a major reactive oxygen species (ROS) and plays diverse roles in plant development and stress responses. However, its localization in large and thick plant organs (e.g. stem, roots and fruits), other than leaves, has proven to be challenging due to the difficulties for the commonly used H2O2-specific chemicals, such as 3, 3’-diaminobenzidine (DAB), cerium chloride (CeCl3) and 2’, 7’-dichlorofluorescin diacetate (H2DCF-DA), to penetrate those organs. Theoretically, the reaction of endogenous H2O2 with these chemicals could be facilitated by using thin organ sections. However, the rapid production of wound-induced H2O2 associated with this procedure inevitably disturbs the original distribution of H2O2 in vivo. Here, by employing tomato seedling stems and fruits as testing materials, we report a novel, simple and rapid protocol to localize H2O2 in those organs using DAB-mediated tissue printing. The rapidity of the protocol (within 15 s) completely avoided the interference of wound-induced H2O2 during experimentation. Moreover, the H2O2 signal on the printing was stable for at least 1 h with no or little background produced. We conclude that DAB-mediated tissue printing developed here provide a new feasible and reliable method to localize H2O2 in large plant organs, hence should have broad applications in studying ROS biology.